2018
DOI: 10.3390/molecules23040770
|View full text |Cite
|
Sign up to set email alerts
|

A New Lignanamide from the Root of Lycium yunnanense Kuang and Its Antioxidant Activity

Abstract: A new lignanamide (1), lyciumamide K, together with four known analogues (2–5), was isolated from the root of Lycium yunnanense Kuang. Based on HR-ESI-MS, NMR spectral data and quantum chemistry ECD calculations, the structure of this new compound was confirmed, including its absolute configuration. Evaluation of the antioxidant activity of compounds 1–5 in the oxygen radical absorption capacity (ORAC) assay showed that they all exhibited significant antioxidant activities. Particularly, compound 1 showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…It is widely cultivated in the arid and semi-arid areas of North and South America, Africa and Eurasia [1]. In China, there are seven species and three varieties that are mainly distributed in the northwest and north parts of the country [2]. In 2008, about 101,171 ha were grown in China with 7845 kg ha -1 as the maximum of yield from elite genotypes [3] while in 2019 the wolfberry cultivated area is over more than 1.33 10 5 ha [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely cultivated in the arid and semi-arid areas of North and South America, Africa and Eurasia [1]. In China, there are seven species and three varieties that are mainly distributed in the northwest and north parts of the country [2]. In 2008, about 101,171 ha were grown in China with 7845 kg ha -1 as the maximum of yield from elite genotypes [3] while in 2019 the wolfberry cultivated area is over more than 1.33 10 5 ha [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, wolfberry fruit provide many amino acids mainly about 11 essential amino acids more than other common berries [9,15]. Moreover, many other compounds were isolated from wolfberry plant including lignanamides, alkaloids, flavonoids, cyclic peptides, lignans, terpenes and phenolic glycosides [2,16].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, only one set of signals could be observed in the 1 H and 13 C NMR spectra (Table ) of compound 9 , indicating that this compound possesses a symmetric structure. The 1 H and 13 C NMR data (Table ) as well as 2D NMR correlations (Figures S83–S86, Supporting Information) indicated that the structure of 9 was highly similar to that of lyciumamide K ( 10 ), a symmetrical feruloyl tyramine dimer fused through a tetrahydrofuran moiety isolated from L. yunnanense Kuang, with the minor differences caused by the 13 C NMR shifts of C-7/7′ (δ C 84.2 for 9 ; δ C 86.2 for 10 ) and C-8/8′ (δ C 58.1 for 9 ; δ C 60.6 for 10 ), which revealed that these two compounds have an identical gross structure. Given the molecular symmetry, four possible relative configurations of the tetrahydrofuran ring could be constructed: 7/8- cis , 7′/8′- cis , 8/8′- trans ( 9a ), 7/8- trans , 7′/8′- trans ,8/8′- cis ( 9b ), all trans ( 9c ), and all cis ( 9d ) (Figure S99, Supporting Information).…”
Section: Resultsmentioning
confidence: 91%
“…The other ten known compounds were identified as lyciumamide K ( 10 ), heliotropamide ( 11 ), tribulusamide A ( 12 ), cannabisin O ( 13 ), lyciumamide A ( 14 ), lyciumamide B ( 15 ), N - E -feruloyl tyramine ( 16 ), N - E -coumaroyl tyramine ( 17 ), (7, 8-ery thro )-1-(4-hydroxy-3-methoxyphenyl)-2-{4-{2-[ N -2-(4-hydroxyphenyl)­ethyl]­carbamoylehenyl-2-methoxyphenoxyl}}-1,3-propanodiolnamed ( 18 ), (7, 8- threo )-1-(4-hydroxy-3-methoxyphenyl)-2-{4-{2-[ N -2-(4-hydroxyphenyl)­ethyl]­carbamoylehenyl-2-methoxyphenoxyl}}-1,3-propanodiolnamed ( 19 ) by comparing the spectroscopic data from the isolated compounds with the data reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical structures of the three amides are similar. It was reported that compound 36 has better activity than compound 35 in inhibiting nitric oxide (NO) release from lipopolysaccharide (LPS)-induced RAW 264.7 cells, suggesting that introducing a methoxy group at the two-position reduces the anti-inflammatory activity of these compounds (Zheng et al, 2018).…”
Section: Amidesmentioning
confidence: 99%